1993
DOI: 10.1007/bf00169996
|View full text |Cite
|
Sign up to set email alerts
|

Rapid measurement of blood leakage during regional chemotherapy

Abstract: In order to avoid complications after regional chemotherapy (isolated hyperthermic perfusion) of the extremities, rapid measurement of blood leakage from the extracorporeal to the systemic circulation is important. A method using technetium-99m in vivo red blood cell (RBC) labelling is reported that provides results within 3 min. Blood samples drawn from the systemic and the extracorporeal circulation were measured for 99mTc activity using a mobile well counter, and the leakage values calculated. The mean resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Shortly after the technique of ILP was introduced, Stehlin et al reported that the leakage factor could be calculated by injecting radioactive iodine-131-labeled human serum albumin in the perfusion circuit and then determining the concentration of the tracer in blood samples from the systemic circulation, drawn at regular intervals [30]. Analog methods, based on the analysis of intermittent blood samples, have been utilized by several groups [31][32][33]. A disadvantage of this approach is that monitoring is neither continuous nor real-time, thus limiting the surgeons' ability to intervene quickly in case of a high leakage or to assess in real-time, whether their interventions restored the isolation of the perfused limb.…”
Section: Leakage Monitoringmentioning
confidence: 99%
“…Shortly after the technique of ILP was introduced, Stehlin et al reported that the leakage factor could be calculated by injecting radioactive iodine-131-labeled human serum albumin in the perfusion circuit and then determining the concentration of the tracer in blood samples from the systemic circulation, drawn at regular intervals [30]. Analog methods, based on the analysis of intermittent blood samples, have been utilized by several groups [31][32][33]. A disadvantage of this approach is that monitoring is neither continuous nor real-time, thus limiting the surgeons' ability to intervene quickly in case of a high leakage or to assess in real-time, whether their interventions restored the isolation of the perfused limb.…”
Section: Leakage Monitoringmentioning
confidence: 99%
“…Many groups have monitored the systemic levels of the drug used exclusively through the analysis of intermittent blood samples. 16,17 However, the flaws in this method are that the monitoring is not continuous and the results take at least 20 minutes before they are known. With this method, the surgeon has no possible chance to intervene rapidly if a potentially dangerous amount of perfusate leaks.…”
Section: Discussionmentioning
confidence: 99%
“…Since Luck 3 introduced the cytostatic agent L-phenylalanine (melphalan) in 1956, it has been the preferred agent in HILP for in-transit metastases of melanoma. Because chemotherapeutic agent dosage is high (up to [15][16][17][18][19][20] times the systemic tolerated dose), a considerable risk of toxic effects is possible due to perfusate leakage into the systemic circulation. 4 Leakage of more than 15% perfusate containing melphalan into the systemic circulation may cause toxic effects such as bone marrow depression, gastrointestinal toxicity, hair loss, and pruritis.…”
mentioning
confidence: 99%
“…In this context, leakage monitoring with blood sampling might be unsuited for toxicity prevention because the results of TNF-a blood concentrations can only be obtained, in the best-case scenario, after a 20-min delay [13,14]. Conversely, using a radiopharmaceutically based technique permits the immediate application of compensatory manoeuvres [13].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, using a radiopharmaceutically based technique permits the immediate application of compensatory manoeuvres [13]. Owing to these advantageous characteristics, the radiopharmaceutical evaluation of systemic leakage in isolated limb perfusion has been extensively validated [7,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%